2013
DOI: 10.1597/11-095
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Tessier 30 and Bilateral Cleft Lip and Palate: A New Clinical Syndrome?

Abstract: Background : Tessier 30 cleft is rare and sparsely reported in the literature. A unique case of an infant with a Tessier 30 cleft, bilateral cleft lip and palate, and other anomalies is presented. In addition to craniofacial anomalies, he had cardiac, gastrointestinal, and genitourinal defects. The constellation of these findings suggests the possibility of a new clinical syndrome. We present these findings and postoperative results following surgical treatment. Patient and Methods : A 37-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The articles were published between 1986 and 2020. Six came from the United States (Al Agili et al, 2004;Becker et al, 2009;Bennett et al, 2018;Cassell et al, 2013Cassell et al, , 2014Zaluzec et al, 2019), two from Vietnam (Swanson et al, 2017;Yao et al, 2016), three from various countries (Adetayo et al, 2012;Carlson et al, 2016;Massenburg et al, 2016), one from Australia (Woincham et al, 2015), one from South Wales (Bhatia & Collard, 2012), one from Sri Lanka (Amaratunga, 1986), one from Brazil (Ise et al, 2019), and one from Nepal (Lindeborg et al, 2020). Regarding the type of study, all were observational studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The articles were published between 1986 and 2020. Six came from the United States (Al Agili et al, 2004;Becker et al, 2009;Bennett et al, 2018;Cassell et al, 2013Cassell et al, , 2014Zaluzec et al, 2019), two from Vietnam (Swanson et al, 2017;Yao et al, 2016), three from various countries (Adetayo et al, 2012;Carlson et al, 2016;Massenburg et al, 2016), one from Australia (Woincham et al, 2015), one from South Wales (Bhatia & Collard, 2012), one from Sri Lanka (Amaratunga, 1986), one from Brazil (Ise et al, 2019), and one from Nepal (Lindeborg et al, 2020). Regarding the type of study, all were observational studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In 2001, Son et al (2001) also presented a case with median cleft of the lower lip and mandible concomitant with double-inlet single ventricle. In 2013, Adetayo and Martin (2013) reported a 37-week-old infant with a Tessier 30 cleft concomitant with levocardia, perimembranous moderate-to-large VSD, patent foramen ovale, double-outlet right ventricle, intestinal malrotation, and bilateral undescended testicles. In 2015, Tafreshi et al (2015) reported the first Iranian case of Tessier 30 of 12-hour-old boy with large VSD, a mild atrial septal defect, and a small patent ductus arteriosus.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Adetayo reported a 37-week-old infant with a Tessier 30 cleft concomitant with levocardia, a perimembranous moderate-to-large ventricular septal defect, a patent foramen ovale, double outlet right ventricle, intestinal malrotation, and bilateral undescended testicles ( 3 ). In 2001, Son also presented a case with median cleft of lower lip and mandible concomitant with double inlet single ventricle ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the cleft can vary from mild notching of the lower lip or mandibular alveolus to complete mandibular, lower lip, and tongue cleavage, which extends to neck structures ( 1 ). Different malformations in other organs such as heart, limbs, and internal organs are also reported concomitant with Tessier 30 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 87%